Geospatial Analysis of Urbanization and its Impact on Land Use Changes in Sargodha, Pakistan - Omar Riaz; Huma Munawar; Muhammad Nasar u Minallah; Kashif Hameed; Maryam Khalid (Journal of Basic & Applied Sciences, 2017)
The focus of this study is on the application of GIS and remote sensing on urbanization and its impact on land use changes in Sargodha from 1992-2015. Sargodha has witnessed rapid urbanization and due to urban expansion many changes have been detected in the land use of Sargodha. For this study, census data, multi-temporal city maps and multi spectral satellite images are used. Landsat TM 1992 and ETM+ 2000, 2005, 2010 and 2015 Landsat 8 are classified using supervised classified method (MLC) to produce land use maps. The classification accuracy has been assessed by calculating kappa index of agreement and ground control points were also collected to verify the results. The results indicate that, over the past 24 years there is a growing trend in urban land use while the agricultural land and all other categories are showing a declining trend since 1992. The total increase in urban land use is 25380.8 hectares and it has increased in 2000, 2005, 2010, and 2015 at the rate of 2.2%, 4.1%, 9.2% and 17.4% respectively. This rapid urbanization resulted into loss of agricultural land. While the overall change observed in agricultural land, water area and bare land is -11008.5, -38926.5 and 9492.7 hectares respectively.